Menciptakan Sekolah Ramah Anak yang Nyaman pada SPS Ananda Sayang Melalui Mural - Nurhadi, Septi Kurniawati; Frananda, Antonius Zannu Fetrix; Hirawati, Nindita (Universitas Nusantara PGRI Kediri, 2023)
Early Childhood is divided into 4 (four) groups, namely fetuses in the womb until birth, newborns up to 28 days of age, ages 1 to 24 months, and ages 2 to 6 years. The development of the human brain begins in the womb, and each period has its development. In supporting children's brain development, it is necessary to have quality nutrition and stimulation from the environment. Development naturally through family or society, while optimal development is through maximum stimulation from Early Childhood Education (PAUD). PAUD aims to build children's readiness to enter further education (school). Child-friendly PAUD will significantly help achieve the intended goal. One of the policies to become a child-friendly school is creating a healthy, beautiful, and comfortable school environment. Ananda Sayang SPS (Similar PAUD Unit) is one of the non-formal PAUDs located in Bintaran hamlet. Currently, PAUD uses the former SD Negeri Bintaran 1 building from the previous one using the house of one of the residents. The purpose of this PAUD is to help the community around the Bintaran area fulfill the stimulation of child development. The entry fee for this PAUD is quite affordable, but this impacts the physical condition, which in some parts looks damaged due to the lack of budget for renovating and adding that the school building is an old building. One way to make SPS Ananda Sayang a child-friendly school is by making a mural that matches the character of early childhood in the school environment. In the process of making murals, as an effort to improve children's brain development, students participate in the form of games (sensory play). It is hoped that the mural can make SPS Ananda Sayang more comfortable to use as a means of learning and playing for students.